2016
DOI: 10.1292/jvms.15-0227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of refractive error on visual evoked potentials with pattern stimulation in dogs

Abstract: The purpose of this study was to investigate the effects of refractive error on canine visual evoked potentials with pattern stimulation (P-VEP). Six normal beagle dogs were used. The refractive power of the recorded eyes was measured by skiascopy. The refractive power was corrected to −4 diopters (D) to +2 D using contact lens. P-VEP was recorded at each refractive power. The stimulus pattern size and distance were 50.3 arc-min and 50 cm. The P100 appeared at almost 100 msec at −2 D (at which the stimulus mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…VEP is classified into flash-stimulated VEP (F-VEP), which uses a flash stimulus, and pattern-stimulated VEP (P-VEP), which uses a contrast-reversing checkerboard pattern stimulus. In our previous studies, the effects of the refractive power of the eye [10] and anesthesia [9] on canine P-VEP were reported, and we measured canine visual acuity using P-VEP [17].…”
mentioning
confidence: 99%
“…VEP is classified into flash-stimulated VEP (F-VEP), which uses a flash stimulus, and pattern-stimulated VEP (P-VEP), which uses a contrast-reversing checkerboard pattern stimulus. In our previous studies, the effects of the refractive power of the eye [10] and anesthesia [9] on canine P-VEP were reported, and we measured canine visual acuity using P-VEP [17].…”
mentioning
confidence: 99%
“…For P-VEP recording, needle electrodes (VEP needle electrodes, Mayo Corp., Nagoya, Japan) were positioned at the inion (external occipital pro- tuberance) as the recording electrode and the nasion (nasal point) as the reference electrode. A plate-type electrode (LE ear electrode, Mayo Corp.) was positioned on the inner surface of the right auricle as an earth electrode, as in previous reports [ 2 , 3 , 4 ] ( Fig. 1
Fig.
…”
mentioning
confidence: 99%
“…Since we had not considered the refractive power of the eye in previous study, so we thought that the results differ from present study. After that, we reported that refractive power of the subject’s eye affects P-VEP wave form [ 3 ], so we recorded P-VEP after correction of refractive power of subject’s eye in this study. Refraction in an eye is the change in direction of light when light passes from the optic media toward the retina [ 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…34 Another study regarding pattern VEP has observed that the refractive power correction directly interferes in the P100 wave latency. 35 This study demonstrated that VEP is a useful tool for assessing the grating VA of Poodles. Moreover, the 41D IOL implant is effective in improving VA after phacoemulsification, in comparison with that to the aphakic group and which is similar to that of the normal eye.…”
Section: Resultsmentioning
confidence: 68%